Aceh Province Economic Convergence Determination - Ar Razy Ridha Maulana; Teuku Zulham; Sartiyah Sartiyah (International Journal of Business, Economics, and Social Development, 2020)
This study analyzes the occurrence of economic convergence between districts / cities in Aceh Province and looks at the factors that can accelerate the economic convergence. This study uses panel data from 23 districts / cities in Aceh Province for the period 2008-2018. The results found from this study are that there has been economic convergence, both sigma convergence and beta convergence, in Aceh Province. Factors that significantly influence economic convergence in Aceh Province are the average length of schooling, life expectancy, and the special autonomy fund. The time needed to get to half the convergence process is 4.10 years with the resulting conditional beta convergence rate of 16.89%.